Independent Learning and Blended Learning Information System Student - Suryari Purnama; Cicilia Sriliasta (International Transactions on Education Technology (ITEE), 2023)
In the Information Systems Department of Raharja University, where blended learning is used, this study intends to describe the propensity for student learning independence. Data analysis is done using percentages utilizing a descriptive quantitative methodology. There were 90 respondents in the study, which included students from the class of 2021 in the department of information systems at Raharja University. An open-ended statement-style questionnaire with a Likert scale was utilized to collect the data. According to the findings, student learning about independence is generally beneficial. Each variable indicative of learning independence yielded analytical results that fell into the group of favorable outcomes. The percentage results for each indicator are as follows: 1) independence from other people is 78%; 2) confidence is 75%; 3) disciplined behavior is 74%; 4) sense of responsibility is 78%; 5) act on own initiative is 75%; and 6) exercising self control is 76%. While using blended learning, teachers can more easily guide their students through the learning process.